Assessment of governmental strategies for sustainable environment regarding greenhouse gas emission reduction under uncertainty - Karasan, Ali; Guendogdu, Fatma Kutlu; Isik, Guerkan; Kaya, Ihsan; Ilbahar, Esra (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2024)
Since greenhouse gas emissions (GHGE) directly impact climate change that affects the environment, human health, society, and ecosystems, the reduction of GHGE is one of the essential actions for the sustainability of the environment. To reduce global GHGE, the United Nations has defined strategies at three levels: government, private, and public. Choosing between these strategies is a difficult process since there are relationships and contradictions among them. The process also includes uncertainties due to some reasons, such as lack of in-formation, social structure, decision makers' hesitancy, and imprecision in the collected data. In this paper, a hierarchically structured methodology based on a decision-making procedure is proposed for the evaluation of the governmental strategies determined to decide the best strategies by integrating expert knowledge and a literature review. For this aim, interpretative structural modeling, cognitive mapping, and inference systems are integrated as a two-stage decision-making methodology based on fuzzy sets to address uncertainties and imprecision in the evaluation of government strategies for GHGE reduction in Turkiye. Based on the results of the first stage, Transportation is determined as the most influential sector for GHGE mitigation. In the second stage, strategies of the transportation sector are assessed and ranked. Promoting the significant public health benefits of low-carbon policies, including increased public transportation and non-motorized mobility is determined as the most appropriate transportation strategy for the governmental action plan regarding the climate change reduction objective. This paper contributes to applying knowledge and experiences from the current environmental characteristics and social fields to the strategic decision of the GHGE reduction area, to streamline its assessment process, provide human-centered solutions, and accelerate governmental actions.
Keywords: Greenhouse gas emissions; Sustainable environment; Multi-criteria decision-making; Fuzzy set theory; OPTIMAL-DESIGN; ENERGY; SYSTEMS; DYNAMICS; WASTE; Environmental Sciences & Ecology